THE INFLUENCE OF INDIVIDUAL CHARACTERISTICS AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Ami Pujiwati; Etty Susanty (Conference In Business, Accounting, And Management (CBAM), 2015)
This study aimed to analyze the factors that affect the characteristics of the individual, work motivation, the ability of individuals, job satisfaction, and employee performance as well as the effect of each variable. Samples were Jabar local government employees as much as 166 people / respondents. The sampling technique was done deliberately. Data processing was performed by using SEM analysis tools SmartPLS. The analysis showed that there is a significant effect on the individual characteristics on work motivation and performance. Furthermore, based on the results of the analysis showed that there are significant effect on the individual characteristics of the ability of the employee. There is a significant effect on job satisfaction on performance; there is an effect on work motivation on job satisfaction. But the results of the analysis on the performance capability of self showed no effect. Â Key words: characteristics of the individual, work motivation, the abilitily to individuals, job satisfaction, SEM SmartPLS, employee performance